Pengaruh Penggunaan Teknologi Informasi Dan Kompetensi Terhadap Efektivitas Kerja Pegawai Kantor Badan Keuangan Aset Daerah Kabupaten Majene - Dahlia Dahlia; Reny Ruswanti (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
The purpose of this study is to examine the influence of information technology and skills on employee performance at the Regional Asset Finance Agency of Majene Regency. In this research methodology, quantitative techniques with a saturated approach were used. All 66 employees at the Regional Asset Finance Agency of Majene Regency were selected as the population of this study. The results of the study show how the use of information technology and affects employee performance efficiency. The above study shows a significant relationship between information technology and competence, evidenced by the calculated f value of 20.198 at a significance level of 5% (p value 0.05 = 0.000). This indicates that the variables of information technology (X1) and competence (X2) jointly influence employee work efficiency at the Regional Asset Finance Agency of Majene Regency.